2019
DOI: 10.35229/jaes.558213
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Waste Management in Turkey

Abstract: An increase in population, energy demand, industrial activities and other technological developments inevitably cause large amount of waste to be produced. It is a known fact that traditional methods for the collection, transportation and disposal of wastes are not capable anymore to prevent health problems and economic losses. Any deficiency in the management of hazardous wastes, which constitute a significant part of solid wastes, has a range of negative effects for environmental health and safety. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It has been observed that the regulations and practices for the recycling of wastes to the Turkish economy are insufficient (Buzkan and Erman, 2020; Rızvanoğlu et al, 2019). Enforcement of sanctions and heavy fines should be implemented to prevent the removal of unregistered waste from its source (Aydın, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the regulations and practices for the recycling of wastes to the Turkish economy are insufficient (Buzkan and Erman, 2020; Rızvanoğlu et al, 2019). Enforcement of sanctions and heavy fines should be implemented to prevent the removal of unregistered waste from its source (Aydın, 2019).…”
Section: Discussionmentioning
confidence: 99%